2019
DOI: 10.3390/ma12142241
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Viscoelastic Properties of Polymeric Interlayers Used for Laminated Glass: Determination of Material Parameters

Abstract: An accurate material representation of polymeric interlayers in laminated glass panes has proved fundamental for a reliable prediction of their response in both static and dynamic loading regimes. This issue is addressed in the present contribution by examining the time–temperature sensitivity of the shear stiffness of two widely used interlayers made of polyvinyl butyral (TROSIFOL BG R20) and ethylene-vinyl acetate (EVALAM 80-120). To that end, an experimental program has been executed to compare the applicab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…The model matched the experiment very well and provided much better estimation than a one-glass-layer limit. For quasi-static loading of laminated glass, the presented examples also validated the time-/temperature-dependent material properties of the ethylene-vinyl acetate or polyvinyl butyral interlayers derived recently by the authors in [ 28 ]. …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The model matched the experiment very well and provided much better estimation than a one-glass-layer limit. For quasi-static loading of laminated glass, the presented examples also validated the time-/temperature-dependent material properties of the ethylene-vinyl acetate or polyvinyl butyral interlayers derived recently by the authors in [ 28 ]. …”
Section: Discussionsupporting
confidence: 77%
“…In the present study, we exploit the results of our extensive experimental program reported in [ 28 ]. Therein, small three-layer cylindrical samples were loaded in dynamic torsion or dynamic single-lap shear under different ambient temperatures and applied frequencies.…”
Section: Experimental Testing On Laminated Glassmentioning
confidence: 99%
See 1 more Smart Citation
“…and their typically high sensitivity to frequency is shown in Figure 3 (selected examples reproduced from [7,17,22]). In this regard, literature projects have been dedicated to the mechanical characterization of interlayers in use for LG systems, under the assumption of various severe conditions of temperature or time loading (i.e., [23][24][25][26][27][28][29][30]). As far as the interlayer composition and the test method both modify; however, different mechanical properties can be derived for a given interlayer material [31].…”
Section: Beammentioning
confidence: 99%
“…Moreover, this study provides also validation of material parameters of two interlayer foils obtained in the previous step of the project [3]. The paper is organised as follows: Section 2 introduces the 2D plane-stress model and presents the constitutive relationships.…”
Section: Introductionmentioning
confidence: 99%